Aberrant expression of kallikrein‐related peptidase 7 is correlated with human melanoma aggressiveness by stimulating cell migration and invasion. Issue 10 (11th August 2017) - Delaunay, Tiphaine; Deschamps, Lydia; Haddada, Meriem; Walker, Francine; Soosaipillai, Antoninus; Soualmia, Feryel; El Amri, Chahrazade; Diamandis, Eleftherios P.; Brattsand, Maria; Magdolen, Viktor; Darmoul, Dalila
Abstract : Members of the tissue kallikrein‐related peptidase (KLK) family not only regulate several important physiological functions, but aberrant expression has also been associated with various malignancies. Clinically, KLKs have been suggested as promising biomarkers for diagnosis and prognosis in many types of cancer. As of yet, expression of KLKs and their role in skin cancers are, however, poorly addressed. Malignant melanoma is an aggressive disease associated with poor prognosis. Hence, diagnostic biomarkers to monitor melanoma progression are needed. Herein, we demonstrate that although mRNA of several KLKs are aberrantly expressed in melanoma cell lines, only the KLK7 protein is highly secreted in vitro . In line with these findings, ectopic expression of KLK7 in human melanomas and its absence in benign nevi were demonstrated by immunohistochemistry in vivo . Interestingly, overexpression of KLK7 induced a significant reduction in melanoma cell proliferation and colony formation. Moreover, KLK7 overexpression triggered an increase in cell motility and invasion associated with decreased expression of E‐cadherin and an upregulation of MCAM/CD146. Our results demonstrate, for the first time, that aberrant KLK7 expression leads to a switch from proliferative to invasive phenotype, suggesting a potential role of KLK7 in melanoma progression. Thus, we hypothesize that KLK7 may represent a potential biomarker for melanoma progression. Abstract : In the present report, we show that KLK7 is an aberrantly expressed melanoma‐produced proteinase. Elevated KLK7 levels decrease cell proliferation and colony formation but induce an increase in cell motility and cell invasion. This effect is dependent on its enzymatic activity. Our results suggest that KLK7 is a potential biomarker for melanoma progression.